2018
DOI: 10.2174/1745017901814010762
|View full text |Cite
|
Sign up to set email alerts
|

Digitized Morphometric Analysis using Maxillary Canine and Mandibular First Molar for Age Estimation in South Indian Population

Abstract: Background:In recent years, the estimation of age in living individuals have become important to solve judicial or civil problems. Secondary dentin deposition occurs as the age advances and can be measured by calculating the reduction in pulp chamber through Noninvasive radiograph techniques.Aim:The aim is to derive precise population specific formulae for age estimation.Materials and Methods:Digitalized Orthopantomography of 150 subjects, was retrieved. The subjects were divided into study and test group. Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…MAE values less than 10 years are considered acceptable in forensic adult dental AE. 35 MAE values for maxillary molars and mandibular molars in this study were comparable to the results of a study on first molars in the Chinese population. 1 MAE values for dental AE using PTVR on linear models of mandibular first molars (8.81) and maxillary canines (8.58) were also similar to the mandibular first molars (9.79) in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…MAE values less than 10 years are considered acceptable in forensic adult dental AE. 35 MAE values for maxillary molars and mandibular molars in this study were comparable to the results of a study on first molars in the Chinese population. 1 MAE values for dental AE using PTVR on linear models of mandibular first molars (8.81) and maxillary canines (8.58) were also similar to the mandibular first molars (9.79) in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Among the various biological markers for age determination, teeth are a crucial indicator of aging 31 . Methods for age determination are mostly based on X-rays, and assess crown formation, mineralization of a tooth, root growth and apex maturation, and order of eruption of the teeth into the mouth 32 , 33 . While these various dental age estimation methods have been confirmed for children and adolescents, there are few reliable methods with low error rates and high reliability for adults and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopic changes in the teeth are considered part of the normal aging process. Typical age‐related changes in the tooth macrostructure include wear, resection, and root resorption (Ilayaraja et al, 2018). In the present study, decreased root length and increased crown length of the canines were observed with age, which are considered to be key teeth for personal identification (Yuwanati, Karia, & Yuwanati, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary canines often have the longest root (Sapkota & Gupta, 2014) and suffer less wear than the other anterior teeth; thus, they are normally the oldest teeth in adults (Cameriere et al, 2007a). Of the posterior teeth, the first molars are selected for assessment, because they show fewer overlaps and superimposition issues on PRs than the premolars (Ilayaraja et al, 2018). The first molars are usually the first permanent teeth to erupt in the oral cavity; hence, they are most likely to exist in the oral cavity for the longest time and play a vital role in mastication.…”
Section: Introductionmentioning
confidence: 99%